Nutrient uptake of the criolla potato (solanum phureja var. galeras) for the determination of critical nutritional levels (2014)
Based on the nutrient uptake of the criolla potato (Solanum phureja var. Galeras), the critical nutritional levels were determined on a farm in the Carrizal district of the municipality of Granada (Cundinamarca). Five fertilizing treatments were used: 0 fertilization (control), commercial control (CC), proposed recommendation + 50% (PR + 50%), proposed recommendation (PR), proposed recommendation - 50% (PR – 50%); organized with a random complete block design with three repetitions and repeated measurements over time; in each one, the material and nutrient absorption were evaluated in four phonological stages; in which the harvest, yield and profitability were measured. It was observed that the dry material increased rapidly until 113 days after planting (dap) and was higher in treatments CC and PR + 50% with 8,818 and 7,743 kg ha-1, respectively. The statistical analysis showed that the elements: N, P, K, Ca, Mg, S, Zn, Cu and B did not present significant differences over time after 77 dap in treatments CC and PR + 50%. There were no significant differences in yield for treatments CC and PR + 50% but there were significant differences between these treatments and the others. The economic analysis showed that treatment CC had the highest profitability, confirming this as the critical level for the Galeras variety in Granada (Cundinamarca).